2020
DOI: 10.1111/fare.12448
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional Family Systems Approach: LGBTQ+ Latino/a Youth, Family Dynamics, and Stressors

Abstract: Objective We developed an intersectional family systems framework to examine how lesbian, gay, bisexual, transgender, and queer (LGBTQ+) Latino/a youth experience stressors stemming from familial resistance to their marginalized LGBTQ+ identities. Background Anti‐LGBTQ+ sentiments surrounding LGBTQ+ young people of color's multiple marginalized identities shape stressors. Specifically, LGBTQ+ Latino/a youth navigate distressing family experiences, yet how such family dynamics influence their well‐being remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…LGBTQ youth, including LGBTQ youth of color, but also deconstruct stereotypical notions of the heteronormative nuclear family that exists at the intersections of gender, sexuality, and race (Schmitz et al, 2020a(Schmitz et al, , 2020b.…”
Section: Resistancementioning
confidence: 99%
“…LGBTQ youth, including LGBTQ youth of color, but also deconstruct stereotypical notions of the heteronormative nuclear family that exists at the intersections of gender, sexuality, and race (Schmitz et al, 2020a(Schmitz et al, , 2020b.…”
Section: Resistancementioning
confidence: 99%
“…For example, Robinson (2018) highlights how familial instability produced by the intersecting combination of poverty, racism, and religious ideologies—and not transnegativity, per se—is what the Latino/a trans youth perceived as non‐affirmation of their gender identity. Similarly, in their interviews with Latino/a LGBTQ+ youth, Schmitz et al (2020) identified the religious ideologies within their participants' families‐of‐origin as contributing to their families' resistance to their sexual and gender identities. Accordingly, clinical interventions and policy solutions aimed at increasing family acceptance must consider the structural constraints of racism and poverty impacting Latinx families.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from Robinson's (2018) study, as well as others in the small literature on LGBTQ family processes, highlight the ways in which race and ethnicity contribute to variation in how a family responds to an LGBTQ loved one. Specifically, there is evidence to suggest that LGBTQ people of certain racial or ethnic groups have distinct experiences in their families-of-origins, ones that are a product of oppressive systems of racism and poverty (Acosta, 2018;Robinson, 2018;Schmitz et al, 2020). For example, in Robinson's (2018) study, the duality of experiencing affection from one's family while also experiencing identity-based prejudice contributed to additional familial strain in context of poverty, race, and family instability.…”
Section: Background the Lgbtq Family Binary And Its Critiquesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study of Chinese SM young adults where perceived low-parental support of sexual orientation was related to psychological maladjustment, Shao et al (2018) highlighted the role of cultural norms such as respect for parents in shaping perceived parent-child relationships. Religiosity and cultural values were also critical components in a qualitative intersectional study of 41 Latinx SM young adults (Schmitz et al, 2020). Many youth experienced familial invalidation and familial religious pressure as stressors as they navigated their identities within the context of their families.…”
Section: Parental Monitoring and Regulationmentioning
confidence: 99%